2019
DOI: 10.1071/fp18314
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effects of exogenous Ca2+ on foxtail millet seedlings under salt stress

Abstract: In the present study, we investigated whether Ca2+ application alleviates salinity-induced damage in foxtail millet (Setaria italica L.). We evaluated the stress-related ion balance, physiological activity and gene expression involved in plant defences against salinity exposure. Twenty-one-day-old foxtail millet was maintained in sand culture for 7 days and subjected to one of seven treatments: half-strength modified Hoagland solution (the control), 1.0% NaCl, 1.0% NaCl+2.5mM Ca2+, 1.0% NaCl+5.0mM Ca2+, 1.0% N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Ca 2+ -phospholipid signaling system communication regulates phospholipids, inositol, fatty acids, and ROS. It also maintains cellular osmotic equilibrium [75]. On the other hand, P is a critical component of biological substances such as nucleic acids, nucleotides, phospholipids, and phosphoproteins making it the most important plant growth macronutrient [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ -phospholipid signaling system communication regulates phospholipids, inositol, fatty acids, and ROS. It also maintains cellular osmotic equilibrium [75]. On the other hand, P is a critical component of biological substances such as nucleic acids, nucleotides, phospholipids, and phosphoproteins making it the most important plant growth macronutrient [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…For biomass, 10 seedlings were randomly selected, washed with distilled water, and weighed using a one hundred thousandth scale. For the chlorophyll content, the supernatant of the fresh leaf samples soaked in dimethyl sulfoxide under dark condition for 3 days was measured using a spectrophotometer at 663 and 645 nm [ 14 ]. For Na + and K + contents of the leaves, 0.1 g dry powder of leaf samples (≤0.25 mm) was digested with a mixture of concentrated HNO 3 and HClO 4 (2:1 V:V) at 370 °C for 3 h, and the contents were then determined via flame photometer (AP1500, AoPu, Shanghai, China) [ 14 , 65 ].…”
Section: Methodsmentioning
confidence: 99%
“…More importantly, foxtail millet has a suitable adaptive ability to change environmental conditions, especially under increasingly intensified land aridification. Foxtail millet has a great potential for salt tolerance due to its strong fibrous root system, high water utilization rate, strong drought tolerance, and salt tolerance potential [ 14 , 15 ]. Nahar et al [ 16 ] found that the salt tolerance of a foxtail millet accession could maintain higher dry matter and grain yield at 6 dS·m −1 salt level.…”
Section: Introductionmentioning
confidence: 99%
“…Foxtail millet [Setaria italica L.], a perennial C4 plant belonging to the family Poaceae (subfamily Panicoideae, tribe Paniceae), is recognised as a particularly important cereal and forage crop in arid and semi-arid regions (Han et al 2019). This ancient crop, originating from China, is grown worldwide owing to its high tolerance to drought and salinity (Werner et al 2005).…”
Section: Introductionmentioning
confidence: 99%